Air Plethysmography: a Critical Evaluation of the Technique in Patients with CVI - Bossuyt, L. E. G.; Neumann, H. A. M. (Phlebologie, 1999)
Air plethysmography (APG) was compared with clinical assessment and light reflection rheography (LRR) in 68 patients with venous insufficiency (129 limbs). The aim of this study was to investigate the possibilities and limitations of this device for general phlebological practice. Out of the 68 patients, 9 were not able to perform the total investigation protocol (13%). The reflux measurement and the ejection capacity of the calf muscle pump correlated well with severe venous disease, but poorly with mild or absent signs of venous insufficiency. Abnormal refill time measured with LRR was in accordance in 82% with increased reflux with APG. A normal refill time was only correlated in 60% of the cases with a normal reflux APG test. It was not possible to distinguish between deep and superficial insufficiency. It is concluded that APG did not turn out to be the handy method for quick and accurate screening of venous insufficiency patients. Its place in the clinical evaluation for venous patients is not yet clear.Die Air-Plethysmographie (APG) wurde verglichen mit der klinischen Untersuchung und der Lichtreflexionsrheographie (LRR) bei 68 Patienten mit chronischer venöser Insuffizienz (CVI). Das Ziel dieser Studie war es, die Grenzen und Möglichkeiten der APG in der phlebologischen Diagnostik zu erfassen. Von den 68 Patienten konnten 9 (13%) das Studienprotokol nicht beenden. Die Korrelation von APG und LRR, wie auch von ambulantem venösen Druck (AVP) und APG-Messungen während körperlicher Anspannung war mäßig. Die Korrelation von Auswurffraktion und der Schwere der Krankheit hingegen waren gut. Es war nicht möglich aufgrund der APG zwischen tiefer und oberflächlicher venöser Insuffizienz zu unterscheiden. Schlußfolgernd kann gesagt werden, daß die APG nicht in der alltäglichen phlebologischen Diagnostik eingesetzt werden kann, da es eine zeitintensive Untersuchung ist und ihr diagnostischer Stellenwert noch besser definiert werden muß.
Keywords: Air plethysmography; chronic venous insufficiency; calf muscle pump function; photoplethysmography